2006
DOI: 10.1136/oem.2005.022558
|View full text |Cite
|
Sign up to set email alerts
|

The triad of shift work, occupational noise, and physical workload and risk of coronary heart disease

Abstract: Background: Shift work, noise, and physical workload are very common occupational exposures and they tend to cluster in the same groups of workers. Objectives: To study the short and long term effects of these exposures on risk of coronary heart disease (CHD) and to estimate the joint effects of these factors. Methods: The study population in this prospective 13 year follow up study of 1804 middle aged industrially employed men was collected at the first screening for the Helsinki Heart Study. The CHD end poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 36 publications
3
58
0
2
Order By: Relevance
“…A later cessation of shiftwork exposure decreases the risk. A recent 13-year follow-up study showed that the relative risk in the 5-year follow-up for shift work was 1.59, while in the 13-year follow-up with more retired workers, it decreased to 1.34 (54). There is also some evidence that night and shift work may have an impact on the metabolic syndrome (58,59) and type II diabetes (60).…”
Section: Shift Workmentioning
confidence: 99%
See 3 more Smart Citations
“…A later cessation of shiftwork exposure decreases the risk. A recent 13-year follow-up study showed that the relative risk in the 5-year follow-up for shift work was 1.59, while in the 13-year follow-up with more retired workers, it decreased to 1.34 (54). There is also some evidence that night and shift work may have an impact on the metabolic syndrome (58,59) and type II diabetes (60).…”
Section: Shift Workmentioning
confidence: 99%
“…Some prospective studies showing a relationship between shift work and CHD controlled for social class (52)(53)(54)(55)(56). A high demand-low control work situation, like that of effort-reward imbalance, may also partly mediate the association between shift work and cardiovascular risk; for example, the prevalence odds ratios for hypertension and atherogenic lipids attributable to effort-reward imbalance were relatively the highest among shift workers as compared with daytime workers (27).…”
Section: Shift Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter are often precursor events of coronary incidents [2,5,21,27]. The relation between stress / distress and acute myocardial infarction is a subject of many epidemiological studies, revealing that myocardial infarct can be easily triggered by external (environmental, social) factors, such as heavy physical and mental work load, violence etc [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%